Teorias raciais, memória e identidade mato-grossense em Gente e Cousas de Antanho (1924-1934), de José de Mesquita - Ghizzi, Lucas Accioly (2024)
The subject of this dissertation is Jose de Mesquita's series of chronicles Gente e Cousas de Antanho. Published between 1927 and 1943 in the Cuiabá newspaper A Cruz, of which Mesquita was the director, the work consists of several texts, including "Crimes Célebres", "O Relógio da Catedral" and "A missa do Espírito Santo". These texts are the focus of this research, serving as a reference for reflection on Mesquita's construction of a Cuiabá identity, in which "Crimes Célebres" is crossed by racial theories existing at the beginning of the 20th century; how these theories were used for this construction of identity is the main objective of this dissertation. The other two aforementioned texts will also be examined from the point of view of identity, but the analysis will focus on discussions about the relationship between memory and identity, thus constituting secondary objectives. A distinct secondary objective of this research covers the publications of the object to be worked on. While Gente e Cousas de Antanho first appeared in A Cruz in 1927, it was later republished in book format in 1978 and 2011. We will focus on the general objectives of each publication, once again concentrating our analysis on the role of memory in the construction of identity. In this way, we believe we have enough tools to visualize the meaning of being from Cuiabá for Mesquita in the writings indicated.